Pengaruh Human Relation dan Beban Kerja Terhadap Kepuasan Kerja Pada Kantor Desa Jagapati di Abiansemal Badung - Pratiwi, Kadek Reza Ayu; Sugianingrat, Ida Ayu Putu Widani; Puja, I Made Suasti (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
The village office is one of the government offices whose job is to serve residents in a village. To be able to serve residents well, the job satisfaction of village office employees is noteworthy. The purpose of conducting this research is to determine the effect of human relations and workload on employee job satisfaction. This research was conducted at the Japapati Village Office in Abiansemal, Badung Regency. The population in this study were all employees of the Jagapati Village Office, totaling 35 people, all of whom were used as research subjects. Data collection methods used were observation, interviews, documentation, literature study, and questionnaires as measured by a Likert scale. The data analysis technique used is multiple linear regression. The results of the determination analysis show that the effect of human relations and workload on job satisfaction is 70.6 percent. The results of the partial significance test prove that human relations has a positive and significant effect on job satisfaction with a regression coefficient of 0.389 (positive) and Sig (0.025) < ? (0.05) and workload has a negative and significant effect on job satisfaction with a regression coefficient of -1.035 (negative ) and Sig (0.000) < ? (0.05). The results of the simultaneous significance test prove that human relations and workload have a significant effect on job satisfaction with Fcount (38.367) > Ftable (3.304) and Sig value (0.000) <? (0.05).